Sowing time and substrate in the production of ipê-mirim seedlings - Ferraz, Marcos Vieira [UNESP]; de Souza, Antonio Maricélio Borges [UNESP]; Costa, Carla Rafaele Xavier [UNESP]; Muniz, Ana Carolina Corrêa [UNESP]; de Andrade Loureiro, Eduardo Akira Suzuki [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2022)
Tecoma stans is popularly known as ipê-mirim in Brazil. This species belongs to the Bignoniaceae family and it is native to Americas and Antilles, where it is widely used in landscaping as urban tree. The seedlings are produced from seeds and there are several factors that influences its development, such as the sowing time and the substrate. This work aimed to understand the effect of the sowing time and substrates on the production of Tecoma stans seedlings. The experiments were carried out in a nursery. The experimental design was completely randomized. The substrates were arranged in a 2 × 6 factorial scheme, two sowing times (autumn and spring) and six commercial substrates (SC1; SC2; SC3; SC4; sand and vermiculite) under four replicates and ten seedlings per plot. The means were compared to each other using the Tukey test (p < 0.05). There was a significant difference between the seasons of the year, showing that the percentage of emergence was higher in spring (89%). The seedlings of Tecoma stans were shown to be nutrient-dependent both in the emergence of the seedling and in the subsequent development of the seedlings, since the highest averages of the studied characteristics were obtained in the commercial substrates, as they have nutrients in their composition, with greater emphasis on SC1
Época de semeadura e substrato na produção de mudas de ipê-mirim
Keywords: Ornamental Plant; Seedling Production; Tecoma Stans; Urban Afforestation